Rabbit as an animal model for experimental research - Manjeet Mapara; Betsy Sara Thomas; K M Bhat (Wolters Kluwer Medknow Publications, 2012)
Animal experimentation is carried out in consultation with the veterinary wing but it is essential that be familiar with experimental protocols of animal model to be able to design an approriate study. This is more so in place where the veterinary facilities are not easily available.Span Rabbits are commonly used as subjects for screening implant material. They have gained favour for their numerous advantages even though they should be ideally used prior to testing in a larger animal model. Though experimentation on rabbits seems to be easy there are many pitfalls. Our endeavor in this article is to integrate all the data about maintaining rabbits as a model and to critically analyze it on the basis of our experimentation.